2009
DOI: 10.1007/s00214-009-0546-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of semiempirical methods for the photoisomerisation of a protonated Schiff base

Abstract: The potential energy surfaces and non-adiabatic dynamics of the C 5 H 6 NH 2 ? protonated Schiff base (PSB3) have been investigated using the OM2 semiempirical Hamiltonian with GUGA configuration interaction. Three approaches to selecting the GUGA-CI active space are evaluated using closed-shell and open-shell molecular orbitals. Energy minima and minimum energy crossing points (MECPs) have been compared with ab initio CASSCF and CASPT2 results. Only the open-shell calculations give a qualitatively correct MEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 39 publications
2
83
0
Order By: Relevance
“…Further detail on the reference calculations can be found in the original publications. 25,26 For HDI, only the CI with phenyl ring torsion was studied using the CASPT2 method; 25 however, both CIs, CI Ph (Scheme 1I) and CI Im (Scheme 1J), were investigated by the CASSCF method. 52 Because the latter approach does not systematically include the dynamic electron correlation, the CASSCF results are not used when benchmarking the density functional calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further detail on the reference calculations can be found in the original publications. 25,26 For HDI, only the CI with phenyl ring torsion was studied using the CASPT2 method; 25 however, both CIs, CI Ph (Scheme 1I) and CI Im (Scheme 1J), were investigated by the CASSCF method. 52 Because the latter approach does not systematically include the dynamic electron correlation, the CASSCF results are not used when benchmarking the density functional calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of several popular density functionals will be investigated in comparison with the results of high-level ab initio multireference wave function calculations available in the literature. 25,26 The results of density functional calculations will be analyzed in chemical terms, where the elementary reaction coordinates of photorearrangement will be employed. 27 In section 2 the properties of conical intersection points and the method of calculation will be briefly outlined.…”
Section: Introductionmentioning
confidence: 99%
“…OM3, a simplified and reparametrized version of OM2, includes corrections to the two-center core Hamiltonian matrix elements to introduce a dependence on the molecular environment by three-center terms and an alternative effective core potential to account for core-valence orthogonalization. It has been reported that the orthogonalization corrections improve the description of orbital-energy patterns, [49,53] electronic excitation energies, [46,53,54] closed shell repulsions, [46] conformational preferences [55] and hydrogen-bonding interactions. [46,56] The improved description of hydrogen-bonding has also been confirmed in combined QM/MM calculations on hydrogen-bonding complexes.…”
Section: Qm/mm Molecular Dynamics Setupmentioning
confidence: 99%
“…To always retain the p orbitals in the active space, we used a recently developed method for identifying and tracking the p character of orbitals (applying a threshold of 0.4 for the sum of the local p populations). 86 In these tests, the calculated excitation energies did not change significantly upon increasing the size of the active space (see below). Hence, the smallest active space (10, 9) was chosen as standard for the OM2-MRCI excited-state calculations, both under vacuum and in HcRed.…”
Section: Excited State Simulationsmentioning
confidence: 89%